Sufistic Psychotherapy Through Wirid Dalail Khairat: Towards A Resilient Mental Character - Ronika, Rima; Bastian, Muhamad Fajar; Sholihah, Inayatus (Al-Ulum, 2025)
Modernization has generated various life challenges that contribute to the rise of mental and psychological disorders, highlighting the need for alternative approaches beyond medical treatment. This study focuses on the Wirid Dalail Khairat as a form of Sufi psychotherapy in addressing mental health issues. The research employs a qualitative method using content analysis to examine the texts and meanings of Dalail Khairat, interpreted through the theoretical framework of Sufi psychotherapy. The findings indicate that the practice of Dalail Khairat contains psychological, moral, and spiritual dimensions that play a significant role in calming the mind, reducing stress, controlling excessive desires, fostering inner peace, and strengthening closeness to Allah. Therefore, Dalail Khairat can be understood as an effective Sufi psychotherapeutic method that contributes positively to individual well-being and quality of life in the context of modern challenges.